Intestinal rearrangement of biliopancreatic limbs, alimentary limbs, and common limbs in obese type 2 diabetic mice after duodenal jejunal bypass surgery - Heng Li; Heng Li; Jipei He; Jie Hou; Chengjun He; Xiaojiang Dai; Zhigao Song; Qing Liu; Zixin Wang; Hongyan Huang; Yunfa Ding; Tengfei Qi; et al. (Frontiers in Endocrinology)
Bariatric surgery is an effective treatment for type 2 Diabetes Mellitus (T2DM), yet the precise mechanisms underlying its effectiveness remain incompletely understood. While previous research has emphasized the role of rearrangement of the gastrointestinal anatomy, gaps persist regarding the specific impact on the gut microbiota and barriers within the biliopancreatic, alimentary, and common limbs. This study aimed to investigate the effects of duodenal-jejunal bypass (DJB) surgery on obese T2DM mice. We performed DJB and SHAM surgery in obese T2DM mice to investigate changes in the gut microbiota and barrier across different intestinal limbs. The effects on serum metabolism and potential associations with T2DM improvement were also investigated. Following DJB surgery, there was an increased abundance of commensals across various limbs. Additionally, the surgery improved intestinal permeability and inflammation in the alimentary and common limbs, while reducing inflammation in the biliopancreatic limbs. Furthermore, DJB surgery also improved T2DM by increasing L-glutamine, short-chain fatty acids, and bile acids and decreasing branched-chain amino acids. This study underscores the role of intestinal rearrangement in reshaping gut microbiota composition and enhancing gut barrier function, thereby contributing to the amelioration of T2DM following bariatric surgery, and providing new insights for further research on bariatric surgery.